A systematic review of determining the input and output variables to measure the school efficiency by data envelope analysis method - Haddad, Meryana Zuhair; Yee, Mei Heong (2021)
In an attempt to support maximize utilization of public funds towards education; this study distilled existing literature to shed light on schools’ efficiency, while focusing on the input and output variables along with data envelopment analysis (DEA). A systematic search of the existing literature was conducted through the relevant scientific databases of ‘Google Scholar’, ‘Scopus’, and ‘Web of Science’, using the keywords: ‘Education Efficiency’, as well as ‘School Performance’, ‘Input and Output variables’. The search resulted in 1550 articles published between the years 2010 and 2020. Following a pre-determined inclusion criteria and a thematic analysis, the findings revealed that school-related factors, student-related characteristics, and external environmental factors aligned to the input variables are the major determinants to drive the most important indicator of education efficiency that is academic performance (output variable). Results gathered from this study are hoped to generate significant insights and benefits for the major stakeholders of public primary education. Apart from enriching the current literature on education efficiency, this study could guide the ongoing educational reforms that are taking place across the globe in a significant and timely manner.